Рекенштейны: [роман] / Вера Крыжановская - Крыжановская Вера Ивановна (Алая Роза, 1994)
Экземпляры: ф13 (20161219) / Инвентарный номер: 53190 / Цена: 50.00 / Сис.шифр: Р1 / Авт.знак: К 85 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1